Managing Networks of Twenty-First Century Organisations - Perri, P. author. aut Link
XIV, 309 p. 3 illus.
Keywords: The book presents a novel theory of how networks of organizations work, what varieties are possible and how their strengths and weaknesses differ. The argument is illustrated using four case studies in which networks of firms and organizations in defence contracting, biotechnology, health care and combating crime and disorder are examined. The book will be of major interest to scholars and students of business and management, public management, public policy, organizational sociology and to practising managers.